The Role of Roscoe Pound's Social Engineering Theory in Realizing Social Justice Through Legal Discovery in Indonesia - Triana, Yeni; Hartono, Wandi; Setiawan, Jetmiko; Muhardi, Dekky (Journal of Social Science and Education Research, 2024)
Roscoe Pound, a well-known legal expert from the United States, said The theory of "social engineering" describes law as a tool to engineer society towards a better order. In this context, the law is not only seen as a set of rules that govern human behavior, but also as a mechanism to create positive social change and realize social justice. The judge in examining and deciding the case, faces a reality, that the written law does not always solve the problem at hand. In fact, often judges often find the law themselves (Rechtsvinding), to complement the existing law in deciding a case. Judges on their own initiative must find the law, because judges should not reject cases on the grounds that the law does not exist, is incomplete, or the law is vague. The method used is normative legal research. Based on the results of the study, it is known that the Role of Roscoe Pound's Social Engineering Theory in Realizing Social Justice Through Legal Discovery in Indonesia that Roscoe Pound's social engineering theory offers a useful framework to understand and improve the role of law in realizing social justice in Indonesia. Through the application of social engineering principles, law can serve as a tool to create positive social change, protect the interests of society, and ensure an equitable distribution of justice. In the Indonesian context, the application of this theory has been seen in various regulations aimed at improving social welfare and overcoming injustice. By continuing to develop and apply social engineering theories in legal discovery, Indonesia can be more effective in facing social challenges and realizing a more just and prosperous society.